PENGARUH TUNJANGAN KINERJA DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN PINRANG - Rahma, Sitti (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
The Ministry of Religious Affairs in Pinrang has developed a work plan that corresponds with the Strategies Planning in which the workplace is expected to match the work and be on time in completion. The study aims to see if performance benefits are influential and the work environment influences the motivation for employees' work at the Ministry of Religious Affairs in Pinrang. The data-collection techniques used in this study are questionnaires with a sample size of 28 employees. The method of analysis in this study, by using linear, regression analysis which is the development of simple, linear regression. Research indicates that performance-support variables have a significant impact on job motivation at the office of the Ministry of Religious Affairs in Pinrang and the work environment has a significant impact on the work motivation for the office of the Ministry of Religious Affairs in Pinrang